Developing an inquiry-based STEAM teaching packet in ecoliteracy for pre-service teachers - Perez Jr., Jose Celso S.; Salic-Hairulla, Monera A.; Magsayo, Joy R.; Nabua, Edna B.; Malayao Jr., Sotero O. (Journal of Education and Learning (EduLearn), 2025)
Education plays a vital role in addressing the current environmental crisis. Integrating ecoliteracy in teacher preparation programs empowers colleges and universities to promote a healthy biosphere by producing pre-service teachers (PSTs) who can develop an ecoliterate student citizenry. Connectedly, ecoliteracy must be taught to PSTs through effective and meaningful learning experiences. Using the research and development (RD) design, this study aimed to develop a teaching packet that incorporates inquiry-based learning (IBL) and science, technology, engineering, arts, and mathematics (STEAM) education to foster ecoliteracy among PSTs. Focus group discussion (FGD) results revealed an opportunity to craft the teaching packet. Ecoliteracy conceptualizations guided the formulation of the packet’s learning outcomes and topics. Eight (8) evaluators assessed the packet’s preliminary version, which satisfied 74% of the indicators in the adapted evaluation tool. After implementing the packet to 38 PSTs, findings reveal a statistically significant increase in conceptual understanding and ecoliteracy levels. Both PSTs and faculty members share positive perceptions towards the teaching packet, though they also suggested further improvements to the material. Overall, the results document the potential of IB-STEAM in fostering PSTs ecoliteracy, showing how innovative and integrative pedagogies are instrumental for effective ecoliteracy instruction in teacher education.